Behavioural methods for the control of examination anxiety : an experimental investigation - Norton, Gary Kenneth (Rhodes University, Faculty of Humanities, Department of Psychology, 1983)
In 1982, it was reported that one in every three students who fail at South African universities, do not pass because of experiences of excessive anxiety resulting from university examinations. A survey conducted amongst student counsellors and counselling services on all South African university campuses, revealed a deficiency of group and individual therapy for this phenomenon of examination anxiety. The cause of this deficiency, was found to be the already excessive demands made on the time of student counsellors. Noting a similar situation at Rhodes University, the present investigation was initiated, with the aim of developing an economical group counselling programme for test anxious students on Rhodes campus. Sixty-four Rhodes students (who identified themselves as test anxious) volunteered for this investigation. These Subjects were randomly assigned to one of four treatment programmes (each divided into two groups, where Group A, N=6 and Group B, N=7) and a wait-list control group (N=12). Three of the treatments featured multicomponent programmes, each offering a cluster of behavioural interventions centred around: Study Skills Training/Counselling; Systematic Desensitisation (Using individually-constructed anxiety hierarchies); Systematic Desensitisation (Using group-constructed anxiety hierarchies). Included in addition, was a single-component treatment, featuring cognitive modification: a component much favoured by local test anxiety counsellors. Given adverse reports concerning the efficacy of single component programmes, when contrasted with multi component treatments, the cognitive modification package was included as a placebo. A battery of measures was used to assess test anxiety and progress made by Subjects to assuage its debilitative effects . The measures included: (a) Six Self-report measures (including a treatment evaluation schedule and the maintenance of a diary of experience by each Subject); (b) Two measures of physiological reactivity, viz. pulse rate and finger sweat print; and (c) One 'observable' measure, that of academic performance. Using these measures, an assessment of the performance gains or losses by each of the Subjects, was made on three occasions: at pre-treatment, post-treatment and 6-month follow-up. In support of the a priori hypotheses, the systematic desensitisation and study skills multicomponent programmes, realised significant gains on all measures over both the placebo and control groups (with exception of the higher score achieved by placebo subjects over that of the study skills group, on the treatment evaluation schedule) . This finding confirmed the superiority of multicomponent programmes over those with only a single component. The systematic desensitisation programmes proved to be the most effective, as measured on self-report and physiological measures. The superiority of group-constructed anxiety hierarchies over those individually-constructed was established. Study skills training helped Subjects to realise and maintain gains on the academic performance measure, although it took many of these subjects six months, before they had fully incorporated the study techniques taught, in with their own study habits. In discussion of the findings, the evident need to match test anxious students to programmes which "best suit" their characteristics, is presented, and solutions proposed. Weaknesses evident in the measuring instruments and research design, are also highlighted for discussion. As part of this experimental investigation, a discussion on the nature of test anxiety and its links with anxiety theory is introduced, together with a review of problems in measuring test anxiety; popular behavioural treatments used to relieve test anxiety; and a survey of test anxiety counselling on South African campuses. Advice for the therapist/counsellor, the academic, and the researcher, are posited in conclusion.
Keywords: Anxiety; Test anxiety